Novos peptídeos sintéticos e estudo da interação com membranas modelo: efeito de modificações no N-terminal na atividade lítica e antimicrobiana - Zanin, Luciana Puia Moro [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Antimicrobial peptides (AMPs) are components of the innate immune system, which are present in the majority of the living organisms and whose interest is growing due to their potent antimicrobial activity against a broad range of microorganisms, coupled with their usually low toxicity to mammalian cells. In an effort to develop short antimicrobial peptides with the same structural characteristics that imparted selectivity to Polybia-MP1 (IDWKKLLDAALQIL-NH2): the relative positioning of acid and basic residues, an acid residue at the N-terminus, hydrophilicity and the broad polar face. MP1 is a potent antimicrobial, antitumoral and non-hemolytic peptide. We generated a peptide named L1A (IDGLKAIWKKVADLLKNT-NH2) and two analogs with N-terminus modifications; one acetylated (Ac-L1A) and other was extrinsic fluorescent labeled with ortho-aminobenzoic acid (Abz) in which the tryptophan was substituted by valine (Abz-L1A-W8V). We analyzed static and time-resolved fluorescence of tryptophan and ortho-aminobenzoic acid were used and showed significant blue shift when peptides are adsorbed in lipid vesicles and the fluorescence quenching by acrylamide showed that fluorophores in anionic vesicles, are less exposed to the solvent than in neutral vesicles. The lytic activity in vesicles showed from dose-response curves that the three peptides were more efficient in anionic vesicles moreover that the analogs were more efficient. These observations were compatible with the higher helical content (observed in Molecular Dynamics and Circular Dichroism) and deeper burying of the fluorophores in anionic vesicle. MD and CD data demonstrated a relationship between the stability of the helix and the absence of load on the N-terminal. L1A and Ac-L1A presented potent antimicrobial selective against Gram negative bacteria without being hemolyitic while Abz -L1A -W8V was mildly hemolytic

Peptídeos antimicrobianos (PAMs) são componentes do sistema imune inato, que estão presentes na maioria dos organismos vivos cujo interesse é crescente devido à sua potente atividade antimicrobiana contra uma vasta gama de microrganismos, juntamente com a sua baixa toxicidade, em geral, para as células de mamíferos. Esse trabalho teve a finalidade de desenvolver um peptídeo antimicrobiano curto com as mesmas características estruturais do peptídeo Polybia-MP1 (IDWKKLLDAALQIL-NH2) extraído da vespa Polybia paulista que conferem ação antimicrobiana e seletividade, tais como: o posicionamento relativo dos resíduos de aminoácidos carregados, um resíduo ácido na posição N-terminal, a hidrofilicidade e a ampla face polar. Foi idealizado e sintetizado um peptídeo denominado L1A (IDGLKAIWKKVADLLKNT-NH2) e dois análogos com modificações na região do Nterminal; um acetilado (Ac-L1A) e outro com o ácido orto-aminobenzóico (Abz), uma sonda fluorescente extrínseca, ligado covalentemente ao N-terminal, esse peptídeo teve o triptofano substituído por um resíduo de valina (Abz-L1A-W8V). Analisou-se a fluorescência estática e dinâmica do triptofano e do Abz, que apresentaram significante deslocamento quando os peptídeos são adsorvidos em vesículas lipídicas; a supressão da fluorescência por acrilamida mostrou que os fluoróforos em vesículas aniônicas estão menos expostos ao solvente do que em vesículas zwitterionicas. A atividade lítica em vesículas a partir das curvas de doseresposta também reforça que os três peptídeos são mais eficientes em vesículas aniônicas, além disso, que os análogos foram mais eficientes. Estas observações foram compatíveis com o maior teor helicoidal (observado em dinâmica molecular e dicroísmo circular) seus fluoróforos se enterram mais profundamente em vesícula aniônica. Dados de MD e CD demonstraram uma relação entre a estabilidade da hélice e a ausência de carga ...
Keywords: Biologia molecular; Biofísica; Dinamica molecular; Peptídeos antibióticos; Agentes anti-infecciosos; Membranas (Biologia); Biophysics